2021
DOI: 10.1097/qai.0000000000002799
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID-19–Related Social Disruptions and Effects on Psychosocial Health in a Mixed-Serostatus Cohort of Men and Women

Abstract: Objectives: This study describes prevention behavior and psychosocial health among people living with HIV (PLHIV) and HIV-negative people during the early wave of the coronavirus disease 2019 (COVID-19) pandemic in the United States. We assessed differences by HIV status and associations between social disruption and psychosocial health. Design: A cross-sectional telephone/videoconference administered survey of 3411 PLHIV and HIV-negative participants in the Multicenter AID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous research has found higher levels of social disruption to be associated with great likelihood of symptoms of depression and anxiety; by contrast, this study measured prepandemic depression, anxiety, and PTSD and the effect of PTSD on COVID pandemic disruptions. 32 Results support that those with pre-existing mental health challenges may be especially burdened by disruptions associated with the COVID-19 pandemic. A bidirectional relationship may exist between social disruption and mental health such that COVID-19 stressors such as fear and anxiety may also exacerbate mental health challenges, and those already living with mental illness may be especially vulnerable to disruptions.…”
Section: Discussionmentioning
confidence: 76%
“…Previous research has found higher levels of social disruption to be associated with great likelihood of symptoms of depression and anxiety; by contrast, this study measured prepandemic depression, anxiety, and PTSD and the effect of PTSD on COVID pandemic disruptions. 32 Results support that those with pre-existing mental health challenges may be especially burdened by disruptions associated with the COVID-19 pandemic. A bidirectional relationship may exist between social disruption and mental health such that COVID-19 stressors such as fear and anxiety may also exacerbate mental health challenges, and those already living with mental illness may be especially vulnerable to disruptions.…”
Section: Discussionmentioning
confidence: 76%
“…36 A study by Friedman et al conducted in the USA demonstrated that both PLWH and people who do not carry HIV who have lower socioeconomic status were affected more by the adverse impacts of COVID-19, resulting in lower resilient coping and other adverse psychosocial outcomes. 37 Also, they found income as the significant predictor for psychosocial health outcomes and stated that financial interventions might be effective in alleviating the negative impact of COVID-19. 37…”
Section: Discussionmentioning
confidence: 99%
“…37 Also, they found income as the significant predictor for psychosocial health outcomes and stated that financial interventions might be effective in alleviating the negative impact of COVID-19. 37…”
Section: Income and Economic Hardshipmentioning
confidence: 99%